Substance Use by Youth with Disabilities and Chronic Illnesses (Second Edition) - Minnesota Univ., Minneapolis. National Center for Youth with Disabilities; Minnesota Univ., Minneapolis. National Center for Youth with Disabilities; Society for Adolescent Medicine, Independence, MO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This annotated bibliography on substance use by youth with disabilities and chronic illnesses lists references published since 1980 that directly address the special developmental needs of adolescents and young adults. The bibliography's scope includes all disabilities and the use or abuse of a wide range of drugs--alcohol, illicit drugs, nicotine, and non-medicinal use of prescribed drugs. The approximately 80 books and journal articles listed are arranged into a general section and a section on training materials. The general section is subdivided by disability type: mental retardation; learning disabilities and attention deficit disorders; mental illness and emotional disturbances; sensory disabilities; other physical disabilities; chronic illnesses; and multiple disability groups. The training materials section describes approximately 20 curricula, booklets, braille materials, and videotapes. A treatment selection checklist concludes the resource guide. The checklist lists questions to ask in selecting a treatment program, based on its philosophy and program structure, treatment components, educational services, aftercare, family involvement, staff, and finances. (JDD)
Availability: National Center for Youth with Disabilities, University of Minnesota, Box 721-UMHC, Harvard St. at East River Rd., Minneapolis, MN 55455 (free).
Sponsoring Agency: Health Resources and Services Administration (DHHS/PHS), Rockville, MD. Office for Maternal and Child Health Services.
Contract Number: MCJ27361-010.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Alcohol Abuse; Chronic Illness; Disabilities; Drinking; Drug Abuse; Instructional Materials; Rehabilitation Programs; Selection; Smoking; Substance Abuse; Tobacco; Young Adults; Reference Materials, Bibliographies; Tests/Questionnaires.